CO2 Thermal Conductivity Detection in Gas Mixture for Concentration Measurement Using Bridge Configuration of Thermopiles - Eko Satria; Melany Febrina; Mitra Djamal; Wahyu Srigutomo; Martin Liess (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
In this research, improvisation was carried out by modifying the market IR thermopile which functions as a thermal conductivity detector to measure the concentration of CO2 gas in the gas mixture. Four thermopiles are configured with a Wheatstone bridge with the aim of increasing the accuracy of the measurement system in detecting changes in CO2 concentration in the gas mixture (N2 and CO2). Using the bridge configuration of these four thermopiles, this measurement system can measure changes in CO2 concentration in small orders. The sensor developed is easy to manufacture, low cost, and has high linearity as evidenced by a correlation coefficient of 0.9943. From the experiments carried out, the sensor works quite accurately in detecting CO2 concentrations with the sensor’s sensitivity of -88.19 Volt/%, the detection range is 0% to 100%, and the RMS error value is 2.25.